Mediation in Land Dispute Resolution for Preventing Criminal Offenses - Dinda Tiara Gisani; Abdul Kadir Jaelani; Fitrat Umirov; Mohd Shafiee Bin Hamzah; Ibnu Mazjah (Sekolah Tinggi Ilmu Hukum Adhyaksa, 2026)
Land disputes remain a persistent legal problem in Indonesia because land holds significant social, economic, and legal value and frequently generates competing claims among individuals and institutions. Unresolved disputes may escalate beyond civil disagreements and contribute to criminal offenses, including unlawful occupation, document falsification, and other unlawful conduct concerning land rights. This study examines the role and effectiveness of mediation in resolving land disputes and preventing related criminal offenses at the Surakarta City Land Office. The research applies an empirical legal method with a qualitative approach by examining the implementation of mediation, institutional practices, and obstacles encountered during dispute resolution. The findings demonstrate that mediation provides an important nonlitigation mechanism for facilitating dialogue, reducing conflict, and encouraging mutually acceptable settlements. However, its effectiveness remains limited by the unwillingness of disputing parties to participate constructively, emotional tensions between the parties, insufficient numbers of competent and certified mediators, inadequate supporting facilities, and limited legal awareness. When mediation fails to produce an agreement, disputing parties generally pursue litigation, which may prolong conflict and increase the possibility of unlawful conduct. The study concludes that strengthening mediator competence, improving institutional capacity, increasing public legal awareness, and encouraging meaningful participation can enhance mediation as a preventive legal mechanism against criminal offenses arising from land disputes.